Correlation between miR‐21 expression and laryngeal carcinoma risks: a meta‐analysis. Issue 1 (February 2016) - Zhou, Peng; Zeng, Fan; Liu, Jun; Lv, Dan; Liu, Shixi
Abstract: Objective: To evaluate the expression and clinical significance of miR‐21 in the tissues of laryngeal carcinoma using meta‐analysis. Methods: Literature databases including PubMed, EMbase, The Cochrane Library, Web of Science, Google Scholar, and the British Library. Two reviewers independently identified the literature according to inclusion and exclusion criteria, extracted data, and assessed the quality of the included studies. Meta‐analysis was performed using Stata 12.0 and RevMan 5.0 software. Results: A total of four studies involving 160 cases were included. No significant heterogeneity was found between studies. The results of meta‐analysis showed high miR‐21 expression was found in Laryngeal cancer than non‐neoplasm tissue (odds ratio = 4.47, 95%CI 2.59 to 7.73, P = 0.02). Only one study reported the expression of miR‐21 between TMN (tumor, metastasis, node) I to II and TMN III to IV. Conclusion: miR‐21expression is notably correlated to laryngeal carcinoma and its clinically pathologic features. It suggests that higher miR‐21 expression may be a risk factor of laryngeal carcinoma and a potential molecular biomarker. For the quantity and quality limitation of the included studies, the conclusion still needs to be further proved by performing more high‐quality studies.